Effects of Vitamin D Supplementation on Inflammatory Markers and Hematological Parameters in Type 2 Diabetes Mellitus - Muhammad Saeed, Sadia Ishaq, Sidra Zahid, Muhammad Imran Bajwa, Sehar Shamshad Ali, Atif Mahmood, Farah Naz Tahir (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
The growing prevalence of Type 2 Diabetes Mellitus (T2DM) has raised concerns about its relationship with inflammatory markers and hematological parameters, both of which are implicated in disease progression and complications. Recent studies suggest that vitamin D, a key regulator of immune function, may play a critical role in modulating these biomarkers. This study investigates the effects of vitamin D supplementation on inflammatory markers and hematological parameters in individuals diagnosed with T2DM.